Microwave wireless power transfer at multiple frequencies / Muhamad Hazwan Wahab - Wahab, Muhamad Hazwan
Microwave Wireless Power Transfer (WPT) Systems one of the alternatives to replace wired power transmission in the modern life nowadays. Directive radiation antenna is used in this system to make sure power transmitted in effective way through microwaves in a long range. This paper describing about the directional radiation microstrip rectangular patch is chosen as antenna to transmit power. The WPT system is created in multiple of frequencies without degrade any performance and can reduce the size of antenna.